Enhancing Elaboration Skills through Integrated STEM-PjBL: A Study on Object Movement and Living Creatures - Ani, Siti Rizqiyah Putri Dwi; Parmin, Parmin; Nugrahaningsih WH , Nugrahaningsih WH (Journal of Innovative Science Education, 2024)
The Merdeka Curriculum aims to foster creative thinking and digital skills. Initial observations revealed a lack of critical thinking, particularly in students' elaboration skills, due to insufficient motivation, which led to passive learning behaviours. Integrated STEM Project-Based Learning (PjBL) is an educational approach designed to address 21st-century challenges by emphasizing project-based learning and providing students with scientific experiences applicable to problem-solving. This study aims to (1) analyze the impact of integrated STEM-PjBL on elaboration skills in the context of object movement and living creatures; (2) assess the extent of this impact; and (3) evaluate the overall effectiveness of integrated STEM PjBL on the topic. The research was conducted at SMP N 1 Sluke and SMP 1 Pancur using a quasi-experimental method with a Control-Group Interrupted Time-Series Design. The study employed pretest and post-test scores as test instruments and questionnaires and observations as non-test instruments. Data analysis was performed using SPSS. The observation results indicated that the experimental class scores were higher than those in the control class. The t-test values at SMP N 1 Pancur and SMP N 1 Sluke were below 0.05, demonstrating statistical significance. Pearson correlation analysis revealed r-values of 0.69 at SMP N 1 Sluke and 0.60 at SMP N 1 Pancur. The determination coefficient analysis showed that integrated STEM PjBL had a 64% impact on elaboration skills at SMP N 1 Sluke and a 72.72% impact at SMP N 1 Pancur. These values indicate that integrated STEM PjBL significantly influences their  elaboration skills.